Schistosome Egg Migration: Mechanisms, Pathogenesis and Host Immune Responses - Costain, Alice H.; MacDonald, Andrew S.; Smits, Hermelijn H. (Frontiers in Immunology, 2018)
Many parasitic worms possess complex and intriguing life cycles, and schistosomes are no exception. To exit the human body and progress to their successive snail host, Schistosoma mansoni eggs must migrate from the mesenteric vessels, across the intestinal wall and into the faeces. This process is complex and not always successful. A vast proportion of eggs fail to leave their definite host, instead becoming lodged within intestinal or hepatic tissue, where they can evoke potentially life-threatening pathology. Thus, to maximise the likelihood of successful egg passage whilst minimising host pathology, intriguing egg exit strategies have evolved. Notably, schistosomes actively exert counter-inflammatory influences on the host immune system, discreetly compromise endothelial and epithelial barriers, and modulate granuloma formation around transiting eggs, which is instrumental to their migration. In this review, we discuss new developments in our understanding of schistosome egg migration, with an emphasis on S. mansoni and the intestine, and outline the host-parasite interactions that are thought to make this process possible. In addition, we explore the potential immune implications of egg penetration and discuss the long-term consequences for the host of unsuccessful egg transit, such as fibrosis, co-infection and cancer development.